Traditions of Antiquity and New Tendencies in Written Greek of the Byzantine Period - Svarevičiūtė, Kristina (Literatūra, 2013)
In the Byzantine period, the norms of written Greek were primarily rooted in the ancient Greek literary tradition and not in the native linguistic competence. The article touches upon the questions linked to the role of rhetorical theory and techniques reinforced by the Greek educational system and the Byzantine Atticism. Particular attention is paid to the different written registers – low, middle, and high –, different styles according to genre and period, and the lack of consistency in writing at all levels.